2016
DOI: 10.1002/mds.26490
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje cell loss in essential tremor: Random sampling quantification and nearest neighbor analysis

Abstract: Objective Purkinje cell loss has been documented in some although not all postmortem studies of essential tremor. Hence, there is considerable controversy concerning the presence of Purkinje cell loss in this disease. To date, few studies have been performed. Methods Over the past eight years, we have assembled 50 prospectively-studied cases and 25 age-matched controls; none were reported in our prior large series of 33 essential tremor and 21 controls. In addition to methods used in prior studies, the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 49 publications
3
61
1
Order By: Relevance
“…However, we did not find any alterations in the morphology of the inferior olivary neurons in our previous study between ET cases and controls [26], so it is unlikely that changes would have been found among ET subtypes, had we chosen to study this brain region. Second, we did not employ stereological methods for PC counts, although the PC counting method in the current study was previously validated with a random sampling approach [10]. Furthermore, the age of onset is self-reported, and the validity of the self-reported age of onset is unknown [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find any alterations in the morphology of the inferior olivary neurons in our previous study between ET cases and controls [26], so it is unlikely that changes would have been found among ET subtypes, had we chosen to study this brain region. Second, we did not employ stereological methods for PC counts, although the PC counting method in the current study was previously validated with a random sampling approach [10]. Furthermore, the age of onset is self-reported, and the validity of the self-reported age of onset is unknown [27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, we observed climbing fiber-Purkinje cell (CF-PC) synaptic abnormalities in the ET cerebellum; compared to controls, ET cases exhibited decreased CF synaptic density and an increased percentage of CFs extending into the parallel fiber (PF) territory [47]. These changes coexist with a host of other pathological changes in PCs in ET, such as a decrease in PC counts [8] and an increase in torpedoes and associated PC axonal pathologies [8,9], although PC loss is a finding that is variably reproduced [1012]. The presence of such pathological changes in the ET cerebellum reinforces the notion that degeneration and reorganization of cerebellar structures may be important for disease progression in ET.…”
Section: Introductionmentioning
confidence: 99%
“…As a surrogate for normal control subjects, patients with ET are affected by a disorder that has not been associated with striatal pathology or dysfunction. Briefly, the pathophysiology of ET involves the cerebellum and connected brainstem areas where imaging and postmortem studies have shown Purkinje cell loss and other histological abnormalities (30,31), probably leading to oscillatory activity in the cerebellothalamocortical circuit (32). On the other hand, patients with the isolated (cervical and cranial) dystonia included in this study offer a disorder with largely recognized striatal mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent clinicopathological studies of ET patients reported deviating results concerning cerebellar pathology. One study comparing 32 ET (mean age 86 ± 6.1 years) patients and 16 age-matched controls using free-floating parasagittal 100 µm thick sections stained for calbindin, without random unbiased stereological methods, demonstrated an 18% reduction of Purkinje cell linear density and its inverse association with torpedo count; another study from the same group comparing 50 ET cases and 25 age-matched controls using a random sampling approach at 217 sites to quantify Purkinje cells along this cell layer reported significant loss of Purkinje cells and greater distances between single Purkinje cell bodies, supporting the neurodegenerative hypothesis of ET [18,21]. Another study comparing 56 ET patients (including 10 with asymptomatic Lewy bodies) and 2 with progressive supranuclear palsy (PSP) (mean age 89 ± 5.6 years) using 5 µm thick paraffin sections with routine and immunohistochemical methods demonstrated no changes in Purkinje cell linear density, while in an earlier study, the same group reported some cerebellar pathology in 7/11 ET patients (superior vermis atrophy, proliferation of Bergman glia) without mentioning Purkinje cell loss or occurrence of torpedoes [16,22].…”
Section: Introductionmentioning
confidence: 79%